N2Phos – an easily made, highly effective ligand designed for ppm level Pd-catalyzed Suzuki–Miyaura cross couplings in water. Issue 20 (7th May 2020) - Akporji, Nnamdi; Thakore, Ruchita R.; Cortes-Clerget, Margery; Andersen, Joel; Landstrom, Evan; Aue, Donald H.; Gallou, Fabrice; Lipshutz, Bruce H.
Abstract : A new, biaryl phosphine-containing ligand, N2 Phos, forms a 1 : 1 complex with Pd resulting in an active catalyst at the ppm level for Suzuki–Miyaura couplings in water, enabled by an aqueous micellar medium. Notably, aryl chlorides are shown to be amenable substrates. Abstract : A new biaryl phosphine-containing ligand from an active palladium catalyst for ppm level Suzuki–Miyaura couplings, enabled by an aqueous micellar reaction medium. A wide array of functionalized substrates including aryl/heteroaryl bromides are amenable, as are, notably, chlorides. The catalytic system is both general and highly effective at low palladium loadings (1000–2500 ppm or 0.10–0.25 mol%). Density functional theory calculations suggest that greater steric congestion in N2 Phos induces increased steric crowding around the Pd center, helping to destabilize the 2 : 1 ligand–Pd(0) complex more for N2 Phos than for EvanPhos (and less bulky ligands), and thereby favoring formation of the 1 : 1 ligand–Pd o complex that is more reactive in oxidative addition to aryl chlorides.